Sui Generis Characteristics of Build-Operate-Transfer (BOT) Agreements in Regional Asset Management - Argerida Barito; Subekti Subekti; Sri Astutik (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
The Build-Operate-Transfer (BOT) Agreement is one of the cooperation schemes between local governments and the private sector in the management of regional assets, especially to finance public infrastructure development without directly burdening the regional budget. However, juridically, BOT has a unique characteristic (sui generis) because it is located at the intersection between the civil law regime and state administrative law. On the one hand, BOT was born from an agreement that is subject to the principle of freedom of contract as stipulated in the Civil Code, but on the other hand, its implementation is greatly influenced by public authority, licensing, and administrative arrangements derived from laws and regulations. This study aims to analyze the juridical characteristics of BOT agreements in regional asset management and determine the tendency of the legal regime that dominates the agreement. The research method used is normative legal research with a statutory approach and a conceptual approach. Primary legal materials include the Civil Code and Government Regulation Number 28 of 2020 concerning the Management of State/Regional Property, while secondary legal materials are in the form of doctrine and the results of previous research. The results of the study show that the BOT agreement has a dual nature, but the dominance of state administrative law is more prominent because of the existence of government authority, supervision, and restrictions on freedom of contract through regulations. Therefore, BOT cannot be understood solely as a private contract, but rather as an agreement with a public character that requires a balance between the certainty of civil law and the public interest. These findings make a normative contribution to understanding the legal position of BOT in the Indonesian legal system.